A Comprehensive Review of Technology Enhanced Teaching and Learning Experiences - Sohan, Md. Arfan Khan; Orpa, Sanjida Alam (English Lecturers and Teachers Association (ELTA), 2025)
In higher education practice, technology is transforming how students learn and are taught, improving access, involvement, and personalization. There is still uncertainty about the long-term implications of technology integration and its impact on equity. The review aims to show how technology tools (e.g., AI, mobile, VR, and LMS) enhance teaching effectiveness and student learning. Thematic analysis, as outlined by Braun and Clarke (2006), was used to identify and analyse patterns within the data. To conduct this review transparently, a thematic analysis was applied to 46 articles published between 2003 and 2025. Themes presented include student engagement, AI personalization, immersive experiences, and mobile or blended learning design. The findings summary highlighted technology-enhanced instructional delivery, adaptive learning, and digital literacy, while also fostering critical thinking. While promising, issues of digital inequity, limited teacher training, and the integration of digital tools into curricula were still acknowledged. Ultimately, the study revealed that educational technology can enhance student engagement, foster personalized learning opportunities, and promote greater flexibility and immersion. However, this technology needs an enabling digital infrastructure, responsive teachers, and differentiated or sustained curricula. The study suggested that strategic planning, political support, and professional development are necessary to effectively integrate educational technology and achieve inclusive learning environments that enable future-ready students to maximize their learning. Keywords : Educational technology; digital learning; personalized learning